An atypical case of disseminated cutaneous leishmaniasis due to Leishmania peruviana in the valleys of Ancash-Peru - Espinoza-Morales, Diego (2017)
We present an atypical case of disseminated cutaneous leishmaniasis in the Sihuas district, located in the Andean valleys of Ancash-Peru. A 62-year-old man with no particular medical history presented multiple lesions located on the inferior abdomen, lumbar region and the right anterior thigh. Histological analysis found leishmanial amastigotes in the lesion sample, the Montenegro reaction was positive for Leishmania spp, and the polymerase chain reaction was positive for Leishmania peruviana. In conclusion, the atypical presentation of this disease may be related to the presence of an uncommon parasite strain or host immune deficiencies. The molecular identification of the etiology for disseminated leishmaniasis, will allow a better understanding of the presentation and proper treatment, as well as associated risk factors.